2020
DOI: 10.1021/acs.jpclett.0c01426
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lattice Strain on the Formation of Ruddlesden–Popper Faults in Heteroepitaxial LaNiO3 for Oxygen Evolution Electrocatalysis

Abstract: A great deal of research has recently been focused on Ruddlesden−Popper (RP) two-dimensional planar faults consisting of intervened [AO] monolayers in an ABO 3 perovskite framework due to the structurally peculiar shear configuration. In this work, we scrutinize the effect of elastic strain on the generation behavior of RP faults, which are electrocatalytically very active sites for the oxygen evolution reaction (OER), in (001) epitaxial LaNiO 3 thin films through by using two distinct single-crystal substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 44 publications
(63 reference statements)
0
22
0
Order By: Relevance
“…The oxygen evolution reaction (OER) is a crucially important process in electrocatalytic water splitting that may be useful for sustainable, clean-energy technology . Because of its high Ni–O covalency and e g = 1 valence band occupancy, the ABO 3 -type perovskite LaNiO 3 (LNO) has been proposed as a promising OER catalyst in alkaline electrolyte solutions. Several approaches including strain engineering, stoichiometry control, and A-site isovalent/aliovalent substitution have been explored to either tune e g filling or enhance Ni 3d–O 2p covalency to boost the OER of LNO. Recent studies demonstrate that Fe (B-site) substitution for Ni is also favorable for OER in LNO. For example, by the simple electrochemical exchange of Fe in the surface region of epitaxial LNO thin films, Bak et al found that the resulting atomic-scale perturbation of oxygen octahedra improves the charge transfer and OER activity.…”
Section: Introductionmentioning
confidence: 99%
“…The oxygen evolution reaction (OER) is a crucially important process in electrocatalytic water splitting that may be useful for sustainable, clean-energy technology . Because of its high Ni–O covalency and e g = 1 valence band occupancy, the ABO 3 -type perovskite LaNiO 3 (LNO) has been proposed as a promising OER catalyst in alkaline electrolyte solutions. Several approaches including strain engineering, stoichiometry control, and A-site isovalent/aliovalent substitution have been explored to either tune e g filling or enhance Ni 3d–O 2p covalency to boost the OER of LNO. Recent studies demonstrate that Fe (B-site) substitution for Ni is also favorable for OER in LNO. For example, by the simple electrochemical exchange of Fe in the surface region of epitaxial LNO thin films, Bak et al found that the resulting atomic-scale perturbation of oxygen octahedra improves the charge transfer and OER activity.…”
Section: Introductionmentioning
confidence: 99%
“…175,176 Chung's group reported the influence of both tensile and compressive strains on the generation behaviors of Ruddlesden-Popper (RP) two-dimensional planar faults in (001) epitaxial LaNiO 3 thin films by using two distinct substrates of LaAlO 3 and SrTiO 3 , as illustrated in Figure 11(F,G). 177 The number of RP faults for SrTiO 3 substrate is about a two times higher than that for the case using the LaAlO 3 , indicating that the RP-fault formation can be improved for the LaNiO 3 film under a tensile strain field. Meanwhile, even fewer misfit dislocations are observed in the film on SrTiO 3 than those in the film on LaAlO 3 , thus confirming that the effective lattice constant of a LaNiO 3 film is enlarged with the generation of RP faults.…”
Section: Electrocatalysismentioning
confidence: 86%
“…In addition to zero-dimensional ionic vacancies, other types of lattice defects were reported to be very effective to boost the OER activity in oxides and hydroxides. ,,, Bak et al demonstrated that the Ruddlesden–Popper (RP) faults, two-dimensional shear intergrowth layers, were highly active for the OER in LaNiO 3 heteroepitaxial thin films. , Furthermore, as directly shown in Figure b by using ABF-STEM imaging, the Ni–O bond length in the [NiO 6 ] octahedra at the RP fault planes was considerably elongated, representing a strong tetragonal distortion. DFT calculations also revealed the higher DOS of Ni 3 d near the Fermi level together with the strong overlap with O 2 p states so as to facilitate the charge-transfer between Ni and the intermediates (O* and OH*).…”
Section: Oer Catalysis On Oxide-based Materialsmentioning
confidence: 99%